Deteksi Dini Risiko Diabetes Melitus Pada Staff Pengajar Stikes Megarezky Makassar - Irwansyah Irwansyah; Ilcham Syarief Kasim (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Diabetes mellitus is a disease caused by a lack or inability of the pancreas to produce insulin at all in the blood, causing various complications that lead to death. Diabetes mellitus sufferers are increasing every year and it is estimated that in 2030 in Indonesia it will reach 21.3 million. Research Objectives: To detect the risk of diabetes mellitus early on the teaching staff of the Mega Rezky Stikes Makassar Research Method is Descriptive Analytic with 42 respondents with propusive sampling technique, data were collected using respondent observation sheets and the results of the study were analyzed in a univariate form. Research results There were 23 respondents (55 %) who have normal blood sugar levels, 13 respondents (31%) are at risk of Type II Diabetes Mellitus and there are 6 respondents (14%) who are identified as sufferers of Diabetes Mellitus. Research Implications: Can be used as a reference for learning, research and scientific development related to conclusions. There are 13 respondents (31%) at risk of Type 2 Diabetes Mellitus Suggestions It is expected that all of the Stikes Mega Rezky Makassar teaching staff to implement a healthy lifestyle as a way to reduce the risk of diabetes mellitus.